Pengaruh Suku Bunga Kredit Terhadap Penyeluran Kredit pada PT BPR “X” Kota Padang - Del Rosa, Yenni (MENARA EKONOMI, 2015)
This study aims to determine the effect of interest rates on loans to the amount of credit inPT BPR "X" of the city of Padang in 2007 - 2014. The data were collected by the methodof historical documentary secondary data based on annual reports time series data. Dataanalysis method used is simple linear regression. PT BPR "X" has Padang city servicesproduct savings and time deposits. The types of loans disbursed in the form of workingcapital loans and consumer credit. Before the data is processed first performed classicalassumption of normality, autocorrelation and heteroscedasticity. The research data werenormally distributed because Jarque Bera test value 4.779383 < 33.924., Does not occurbecause the value of Durbin Watson autocorrelation 1,257 and does not occur becausethe value Park heteroskedastisitas 0.704> 0.05. Because all the classic assumptionfulfilled the importance of the simple linear regression equation Y = 51.325 - 2,138X + ewith the interpretation of the value of a = 51.325 means that if the loan interest rate Rp 0,- the amount of loans disbursed Rp 51.325, -. The value of b = -2.138 means if lendingrates rose Rp 1, - the amount of loans disbursed fell Rp 2.138, -. Partial hypothesis test ata significance level of 5% shows that lending rates had no significant effect on the numberof loans disbursed since 0.045 < 0.05.Keywords: mortgage interest rates and the amount of credit.